PENGGUNAAN METODA FUZZY TSUKAMOTO UNTUK MENENTUKAN PRODUKSI BARANG ELEKTRONIK - Sigit Auliana; Umar Mansyuri (LPPM Universitas Bina Bangsa, 2022)
The Tsukamoto method is one of the methods in the decision-making system in which every consequence of the IF-THEN rule must be represented in a fuzzy set with a monotonous membership function. The application of the Tsakamoto Method in a Decision Support System determines the production of electronic goods so that demand for goods is fulfilled using a decision support system. In this study there are 4 processes used, namely the process of fuzzification, the process of inference/evaluation of rules, composition/aggregation, and defuzzification.The conclusion with the Fuzzy Tsakomoto method in the Decision Support System for determining electronic goods according to demand, can facilitate the process of making reports